The Influence of Liquidity, Solvency and Efficiency Ratio on Conventional Banking Financial Performance For the 2019-2022 Period - Meita Sekar Sari; Maureen Marsenne; Hanif; Suhendar, Suhendar (International Journal of Economics (IJEC), 2023)
This research aims to empirically prove the influence of liquidity, solvency and efficiency on financial performance in banking companies on the Indonesia Stock Exchange. The object of this research is a banking company for the 2019-2022 period. The sampling method uses purposive sampling, where sampling uses several criteria, so the final sample is 32 samples. The data analysis method uses multiple linear regression tests. So the results of this research are that liquidity has a negative and significant effect on financial performance. Solvency has a negative and significant effect on financial performance. Efficiency has a negative and significant effect on financial performance. Liquidity, solvency and efficiency have a significant effect on financial performance.